Specification for general requirements for rotating electrical machines Part 69. Tolerances (BSI, 1972)
Rotating electric machines, Tolerances (measurement), Efficiency, Power factor, Rotation velocity, Electric current, Transient voltages, Electrical reactance, Voltage control, Voltage fluctuations, Inertia, Torque, Moment of inertia